"Nuestra captividad": Captivity and religious difference in an early seventeenth-century translation of the Epistola Rabbi Samuelis (1339). Issue 2 (3rd April 2017) - Giles, Ryan D.
ABSTRACT: This study concerns a manuscript authored by Diego de la Torre (Lilly Sp. Hist. 1628), an Andalusian Carmelite who was taken captive in the 1620s and brought to Tunis. The manuscript begins with a prologue to his Spanish translation of the Epistola Rabbi Samuelis, a fourteenth-century Latin polemic concerning the captivity of the Jews. The prologue is dedicated to a French nobleman and fellow captive, Thomas d'Arcos, who infamously converted to Islam and whose name has been consequently blotted out in the manuscript. A close reading of the text that follows sheds further light on the translator's perspective as a "captivo" in the preliminaries of the epistle. It shows how Diego de la Torre's version of the Epistola— as an example of what Clem Robyns has theorized as a "defensive translation"—associates Christian enslavement with notions of Jewish captivity, and also expresses anxieties over maintaining religious difference and the threat of apostasy in Muslim North Africa during the early seventeenth century.